The Effects of Determinants of Government Expenditure on Education and Health: Evidence From SADC Economies - Mhlari, Horisani; Mosikari, Teboho Jeremiah (Journal of Reviews on Global Economics, 2020)
Health and education expenditure play a major role in determining the well-being and development of the people. However, SADC economies have poor health and education indicators, despite high expenditure by governments. The purpose of this study is to assess the determinants of government expenditure on health and education in SADC countries. This study used the annual data covering the period 1997 to 2017. FMOLS1 and DOLS2 are applied to estimate the parameters of each variable understudy. The techniques were developed to estimate and test hypothesis about cointegrating vector to panel data. Overall the results revealed that gross domestic product, population growth and corruption are crucial determinants of health and education expenditure in SADC countries. Therefore, governments in SADC can implement policy that are pro economic growth, and measures that discourages corruption. This can be achieved by allocating high budget on education expenditure, and implementing independent corruption agencies.